2001
DOI: 10.1016/s0960-9822(01)00399-2
|View full text |Cite|
|
Sign up to set email alerts
|

The anaphase inhibitor Pds1 binds to the APC/C-associated protein Cdc20 in a destruction box-dependent manner

Abstract: An essential aspect of progression through mitosis is the sequential degradation of key mitotic regulators in a process that is mediated by the anaphase promoting complex/cyclosome (APC/C) ubiquitin ligase [1]. In mitotic cells, two forms of the APC/C exist, APC/C(Cdc20) and APC/C(Cdh1), which differ in their associated WD-repeat proteins (Cdc20 and Cdh1, respectively), time of activation, and substrate specificity [2, 3]. How the WD-repeat proteins contribute to APC/C's activation and substrate specificity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 22 publications
4
76
2
Order By: Relevance
“…The mutation of this binding site in Cdh1/Hct1 inhibited cyclin A association to Cdh1/Hct1 and cyclin A degradation (Sorensen et al, 2001). A second study demonstrated that the APC substrate, Pds1, whose degradation is exclusively induced by APC Cdc20 , binds directly Cdc20, whereas it is incapable of associating with Cdh1/Hct1, indicating that Cdc20 and Cdh1/Hct1 recognize and bind their substrates differently and selectively (Hilioti et al, 2001). Further specific and direct interactions of Cdc20 with Pds1 and of Cdh1/Hct1 with Clb2, Clb3 and Cdc5 were also demonstrated in budding yeast (Burton and Solomon, 2001;Schwab et al, 2001).…”
Section: Substrate Recognitionmentioning
confidence: 97%
“…The mutation of this binding site in Cdh1/Hct1 inhibited cyclin A association to Cdh1/Hct1 and cyclin A degradation (Sorensen et al, 2001). A second study demonstrated that the APC substrate, Pds1, whose degradation is exclusively induced by APC Cdc20 , binds directly Cdc20, whereas it is incapable of associating with Cdh1/Hct1, indicating that Cdc20 and Cdh1/Hct1 recognize and bind their substrates differently and selectively (Hilioti et al, 2001). Further specific and direct interactions of Cdc20 with Pds1 and of Cdh1/Hct1 with Clb2, Clb3 and Cdc5 were also demonstrated in budding yeast (Burton and Solomon, 2001;Schwab et al, 2001).…”
Section: Substrate Recognitionmentioning
confidence: 97%
“…Ubiquitination of securin by APC/C requires the binding of the WD40-repeat-containing Cdc20 protein, which recruits substrates to APC/C (Fang et al, 1998b;Hilioti et al, 2001;Pfleger et al, 2001;Harper et al, 2002;Peters, 2002). It turns out that the spindle checkpoint interferes with the productive interaction between APC/C and Cdc20 (Yu, 2002).…”
Section: Molecular Components Of the Spindle Checkpointmentioning
confidence: 99%
“…Under normal conditions, the anaphase-promoting complex/cyclosome (APC/C) 1 promotes the ubiquitination of Pds1, leading to its degradation, and consequently the activation of Esp1 (13,14). The ability of the APC/C to ubiquitinate Pds1 depends on the physical association between Pds1 and an APC/C-associated protein, Cdc20 (15)(16)(17)(18). Specifically, abolishing the binding of Pds1 to Cdc20 prevents Pds1 ubiquitination (17,18).…”
mentioning
confidence: 99%
“…The ability of the APC/C to ubiquitinate Pds1 depends on the physical association between Pds1 and an APC/C-associated protein, Cdc20 (15)(16)(17)(18). Specifically, abolishing the binding of Pds1 to Cdc20 prevents Pds1 ubiquitination (17,18). Cdc20, and its homolog Cdh1, belong to a family of WD-repeat proteins that confer substrate specificity to the APC/C (15,16).…”
mentioning
confidence: 99%